Evaluation of Nootropic Potential of Herbal Extract in Stressed Rats - Geetha, K.M.; Priyadharshini, S.R.B.; Murugan, V. (Asian Journal of Chemistry, 2010)
An ethanolic extract containing a combination of the roots of Withania somnifera and leaves of Ocimum sanctum was investigated for its nootropic activity in stressed rats. Cold swimming for 5 h induced stress. Learning and memory was assessed using the brightness discrimination apparatus. Stress induced impairment of learning and memory in rats was reversed by the combined extract when administered orally for 7 d at 100 mg/kg b.w. However the combined extract was found to be ineffective on a single acute administration.